CIDADES INTELIGENTES: DIGNIDADE HUMANA E DIREITO A UM MEIO AMBIENTE SUSTENTÁVEL - FRANCO GUERINO DE CARLI (2020)
This dissertation addresses smart and human cities, taking into account aspects of urban law, sustainable development and human rights. The proposed analysis concerns the presence of a relationship between smart and human cities and the promotion of Human Rights. A growing phenomenon in recent decades has been a marked urbanization, resulting in enormous challenges for the management of cities, in addition to bringing harmful consequences to the quality of life of its citizens. UN data try to treat a path of no return, with a tendency to worsen in the coming years. Much has been discussed about how to increase the level of intelligence in cities and interest in the topic Smart cities has grown, in an attempt to mitigate this situation. There is still no consensus on a concept of smart city, and it is this that the authors differ on the aspects that can be used to understand a city as smart. Most concepts discuss the concept of the smart city based on the implementation of technologies in cities. Others include, in addition to technology, or human being, as the main actor, and should be an integral part of the entire process of improving cities. Based on this observation, the present work seeks to answer the following research problem: "What is the relationship between intelligent ideas about cities and respect for human rights?". Urban spaces must be built for more attractions, so that people feel invited to be part of the city scene, so that they can live in the city. In order to achieve these objectives, the deductive approach was used, with a bibliographic search. It reached a conclusion about the city in which it is possible to implement aspects of the concept of Intelligent and Human Cities, providing more levels of residents, greater dignity and quality of life, thus allowing greater effectiveness to the human rights of people living in urban centers.